Transformation of the Research of the Professional Activities - Poviliūnas, Arūnas (Sociologija. Mintis ir veiksmas, 2010)
The aim of the article is to analyze how the accomplishment of the research of the professional activities has changed its initial conception and methodology. The initial conception of the research of professional activities was elaborated in the framework of the Lithuanian National System of Qualifications. The article maintains that Lithuanian National System of Qualifications is based inter alia on the premises of structuralism. After the revision of structural approach the article elaborates the alternative conceptualization of the research of professional activities that is based on sociology of P. Bourdieu including the key concepts of field, habitus and capital.